2005
DOI: 10.1103/physrevc.72.021601
|View full text |Cite
|
Sign up to set email alerts
|

Survival of orbiting inNe20(7–10 MeV/nucleon) +C12

Abstract: The inclusive energy distributions of fragments with Z ≥ 3 emitted from the bombardment of 12 C by 20 Ne beams with incident energies between 145 and 200 MeV have been measured in the angular range θ lab ∼ 10 • -50 • . Damped fragment yields in all cases have been found to be characteristic of emission from fully energy equilibrated composites; for B, C fragments, average Q-values, < Q >, were independent of the centre of mass emission angle (θc.m.), and the angular distributions followed ∼1/sinθc.m. like vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Our mean-field calculations with the SLy4 parametrization [30] predict that 70 Ca is bound while 72 Ca is unbound. This is in general agreement with other mean-field calculations of various types [19,31]. However, 72 Ca ( 70 Ca+n+n) is bound in a three-body calculation where the two-body subsystems are unbound.…”
supporting
confidence: 91%
“…Our mean-field calculations with the SLy4 parametrization [30] predict that 70 Ca is bound while 72 Ca is unbound. This is in general agreement with other mean-field calculations of various types [19,31]. However, 72 Ca ( 70 Ca+n+n) is bound in a three-body calculation where the two-body subsystems are unbound.…”
supporting
confidence: 91%
“…Since our measurement was biased towards the higher multiplicity events, it can be inferred that the γ-rays are emitted from a fully energy equilibrated composite. Our earlier charge particle experiments [12,31], for the same reaction, clearly revealed that the damped fragments (Z=3-7) are emitted from a fully energy equilibrated composites and follow a 1/sinθ cm angular dependence. Therefore, the contribution to the high energy component from incomplete fusion and deep-inelastic process can be completely ruled out.…”
Section: Resultsmentioning
confidence: 76%
“…Ichikawa et al, emphasized the inclusion of the rotational energy contribution and showed that the nuclear densities in the SD band become cluster-like at high angular momentum (J). Experimentally, the inelastic scattering and the damped fragment yields, in the reaction 20 Ne + 12 C, indicated the survival of an orbiting dinuclear system [10][11][12]. It is now well known that these cluster structures are associated with strongly deformed shapes of nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…The BCS equations are obtained by taking λ 2 = 0 in the LN equations (5)- (12) with λ 1 being the Fermi level. For this special case Eqs.…”
Section: Lipkin-nogami Equationsmentioning
confidence: 99%
“…This implies that any theoretical model which aim is to describe the properties of exotic nuclei must consider the coupling with the continuum spectrum of energy. Many of such theoretical models are described in references [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%